Pengaruh Model Pembelajaran Reciprocal Learning Terhadap Kemampuan Menulis Puisi Pada Siswa - Yanti Claudia Sinaga; Rosmawaty Harahap (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of this study was to find out how the sharing learning model has an impact on the ability to write poetry in class VIII students of SMP Negeri 8 Medan in the 2022/2023 academic year. This research involved all students in class VIII SMP Negeri 1 Delitua, a total of 303 students in 10 classes. Of the 303 students, 29 were selected to be the research sample. This study uses a one-group pre-test post-test experimental design. The method used is a description test. Test